Impact of Total Shoulder Arthroplasty on Golfing Activity. Issue 4 (July 2015) - Papaliodis, Dean; Richardson, Nicholas; Tartaglione, Jason; Roberts, Timothy; Whipple, Richard; Zanaros, George
Abstract : Objective: Golf is a widely popular sport in the United States with 29 million Americans participating in the game. With an aging population and increased incidence of glenohumeral degenerative arthritis, the number of active golfers requiring total shoulder replacement is on the rise. This study aims to evaluate the effect of total shoulder replacement on golfing activity. Design: Retrospective; questionnaire. Setting: Survey. Participants: Three hundred sixty-seven patients were identified based on Current Procedural Terminology codes who underwent total shoulder arthroplasty (TSA) between January 2004 and January 2013. Interventions: A voluntary anonymous questionnaire was sent to patients by mail including both objective and subjective questions about their level of golf activity and ability both before and after the surgery. Main Outcome Measures: Two hundred sixty-eight (73%) patients responded with 35 (34 right-handed and 1 left-handed patients) golfers completing the questionnaire. Results including visual analog pain scores, handicap change, and driving distance were evaluated statistically using the Student t test. Results: Thirty-five golfers at an average time of 3.2 years after TSA completed the questionnaire with 31/35 being able to return to the sport at an average time of 8.4 months postoperatively. Thirty of 31 patients reported improvement in their pain level during and after golfing activity by an average of 4.3 ( P < 0.05) on a visual analog scale (VAS) for pain. On average, driving distances increased by 12.5 yd ( P = 0.0012) and handicap improved by 1.4 strokes ( P = 0.03). Conclusions: Patients who undergo TSA for primary glenohumeral arthritis can safely return to golfing activity with a significant decrease in their perceived pain level as per VAS scores. Statistically significant findings included an increase in driving distance by 12.5 yd and an improvement in handicap by 1.4. Clinical Relevance: In counseling patients, it is the authors' opinion that based on our experience with golfers undergoing TSA, patients can safely return to sport at an average of 8.4 months. The likelihood of return to play was quite high, but not 100%, and as such no guarantee should be provided to patients. Outcomes of patients with TSA desiring a return to golf are positive, and possible benefits include improvement of pain and possible improvements in driving distance and handicap. Level of Evidence: IV. Abstract : Supplemental Digital Content is Available in the Text.